Controle estereoquímico na preparação de calcogenetos vinílicos - Santos, Paulo César Silva dos (2004)
We describe here a quite general method for the synthesis of vinylic chalcogenides by a nucleophilic vinylic substitution. Thus, the treatment of sodium chalcogenolates with (E) and (Z)--bromostyrenes allows the preparation of the desired products in very large scale and using inexpensive reagents. The reaction was observed to occur with total retention of configuration of the starting vinylic halide, and good yields of the products were obtained. The reaction showed to be applicable also to deactivated vinylic halides, as can be seen on Scheme 1. The methodology is based on the cleavage of diaryldichalcogenides with NaBH4 in ethanol. Substitution of ethanol by DMF under heating, followed by addition of the convenient vinylic halides furnishes the desired product ...